Subsolar Electron Temperatures in the Lower Martian Ionosphere. Issue 2 (17th February 2020) - Peterson, W.K.; Andersson, L.; Ergun, R.; Thiemann, Ed; Pilinski, Marcin; Thaller, S.; Fowler, C.; Mitchell, D.; Benna, M.; Yelle, R.; Stone, Shane
Abstract: Martian subsolar electron temperatures obtained below 250 km are examined using data obtained by instruments on the Mars Atmosphere Evolution Mission (MAVEN) during the three subsolar deep dip campaigns and a one‐dimensional fluid model. This analysis was done because of the uncertainty in MAVEN low electron temperature observations at low altitudes and the fact that the Level 2 temperatures reported from the MAVEN Langmuir Probe and Waves instrument are more than 400 K above the neutral temperatures at the lowest altitudes sampled (~120 km). These electron temperatures are well above those expected before MAVEN was launched. We find that an empirical normalization parameter, neutral pressure divided by local electron heating rate, organized the electron temperature data and identified a similar altitude (~160 km) and time scale (~2, 000 s) for all three deep dips. We show that MAVEN data are not consistent with a plasma characterized by electrons in thermal equilibrium with the neutral population above 100 km. Because of the lack data below 120 km and the uncertainties of the data and the cross sections used in the one‐dimensional fluid model above 120 km, we cannot use MAVEN observations to prove that the electron temperature converges to the neutral temperature below 100 km. However, the uncertainty of the electron temperature altitude profile below 120 km does not impact our understanding of the role of electron temperature in determining ion escape rates because ion escape is determined by electron temperatures above 180 km. Key Points: Observations of Martian subsolar electron temperatures below 160 km from MAVEN deep campaigns are reported and analyzed The observed electron temperatures are significantly higher than those expected before the MAVEN was obtained Electron neutral temperature equilibrium occurs below 100 km